1972
DOI: 10.1002/j.1537-2197.1972.tb10153.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytotaxonomy of Three Sonchus Species

Abstract: All hybrid plants from interspecific crosses among the three species, Sonchus asper (L.) Hill, S. oleraceus L., and S. arvensis L., were male‐sterile, but the progeny of the cross S. arvensis X S. oleraceus and reciprocal cross produced seed after backcrossing to the male parent. Hybrid plants from crosses between S. oleraceus and S. asper lacked vigor. Cytological data indicated that S. arvensis has one genome in common with S. asper and that S. oleraceus is an autotetraploid (2n = 36) with no genomes in comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Barber (1941) de-scribed a few sterile hybrids which had arisen spontaneously in cultivation, but reported that he had been unable to cross these species artificially. Hsieh et al (1972) (1948) listed 23 species of insects found on annual sow-thistles in Britain. Schroeder (1973) …”
Section: Geographical Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Barber (1941) de-scribed a few sterile hybrids which had arisen spontaneously in cultivation, but reported that he had been unable to cross these species artificially. Hsieh et al (1972) (1948) listed 23 species of insects found on annual sow-thistles in Britain. Schroeder (1973) …”
Section: Geographical Distributionmentioning
confidence: 99%
“…Laiteron rude (Alex et al Cayouette l9'71). Compositae, composite 1980), chaudronnet, laiteron 6pineux, lai-family, Compos6es. teron Apre (Ferron et Cayouette l97l (Mulligan 1957), the U.S.A. (Hsieh et aL 1972) and Europe (Barber 1941; Walter and Kuta l97l). Boulos (1913) (Zenari 1921(Zenari ,1924Lewin 1948 (Kennedy et al 1962, Duffus 1971.…”
mentioning
confidence: 99%
“…S. asper has been represented uniformly by diploid plants (somatic chromosome number 2 n = 18) in Europe, USA, and Canada, while S. oleraceus has typically been reported with a chromosome number of 2 n = 32 in Eurasia, Africa, and North America [11,16,17,18,19,20]. However, descending aneuploid (2 n = 16; from Eurasia) and tetraploid (2 n = 36; from North Dakota, USA) chromosome counts also have been rarely reported [16], although the taxonomic identity of the plant material studied remains unclear. Stebbins et al [21] proposed an amphidiploid origin for S. oleraceus ( n = 16, 2 n = 32), which has combined S. asper ( n = 9, 2 n = 18) and S. tenerrimus L. ( n = 7, 2 n = 14).…”
Section: Introductionmentioning
confidence: 99%
“…But a diploid form of S. oleraceus (2n= 16) and tetraploid (2n= 32) were previously reported by Marchal (1920) and Cooper & Mahony (1935), respectively. More studies had described S. asper as diploid (2n= 18) and S. oleraceus as tetraploid (2n= 32) (Turner et al 1961;Walter & Kutta 1971;Boulos 1972;Hsieh et al 1972;Gupta & Gill 1983;Sidhu et al 2011;Kaur & Singhal 2015). The variation of chromosome number in Sonchus species points towards the incidence of aneuploidy that has happened over time in the genus Sonchus.…”
Section: Resultsmentioning
confidence: 99%
“…Morphological features of a leaf (arrangement, shape, type, color), stem (glabrous, hairy), flower (colour, type, shape), androecium (number, shape, nature), gynoecium (shape, number, nature) were examined to establish the identity of each of the three Sonchus species. The available literature (Hooker 1882;Bamber 1916;Turner et al 1961;Walter & Kutta 1971;Boulos 1972;Hsieh et al 1972;Nair 1978;Mejias & Andres 2004;Cho et al 2019) have been looked into to describe the Sonchus species in question. The Herbarium, Department of Botany, Panjab University Chandigarh and online Herbaria have also been consulted for identification.…”
Section: Morphological Studymentioning
confidence: 99%